Neurobrucellosis in a Patient with Multiple Sclerosis; a Case Report: - Sharifian, Maryam; Petramfar, Peyman; Nikseresht, Alireza; Davarpanah, Mohammadali; Nemovi, Masoud; Sharifian, Amirhossein (Galen Medical Journal, 2014)
Background: Neurobrucellosis is a rare complication of brucellosis. Acute meningitis and encephalitis are the most common clinical manifestations; however, symptoms of these two conditions may be subacute and diagnosis requires a high index of suspicion in patients from endemic areas. Diagnosis is often based on neurological symptoms, serology, and suggestive brain imaging because cerebrospinal fluid culture yields are low. Case report: Herein we report a 30 year old female a known case of MS (Multiple Sclerosis) who presented with ataxia and agitation, in physical examination the patient had ataxic gait and decreased concentration, Brain MRI showed significant brain atrophy and hydrocephaly. Laboratory workups showed a lymph dominant leukocytosis. ESR and CRP rose significantly. CSF (Cerebrospinal fluid) was obtained and sent for cell count and chemistry analysis. The CSF analysis showed 1734 mg/dl protein, 254 leukocytes (80% lymphocyte). Complete blood count (CBC) showed lymph dominant leukocytosis. Wright test in CSF was positive. Accordingly Neurobrucellosis was considered as the cause. Conclusion: Due to several of immunomodulating or immunosuppressive treatments in the patients with MS, and Chronic suppression of cell-mediated immunity these patients may be more prone to infections. So in such patients careful evaluation of clinical findings are of great importance.